FRAMING DAN REPRESENTASI GENDER DALAM MUSIK VIDEO DAN LIRIK LAGU "OSHIBE TO MOSHIBE YORU NO CHOUCHOU" JKT48: ANALISIS KRITIS - Ferdy Salsabilla; Bagas Rachmad Eka Putra; Andi Fyqri Hanyfa Lemppa (Sintesa, 2026)
Music videos, as products of popular culture, function not only as a form of entertainment but also as sites of meaning production that represent social relations, including gender constructions. This article examines gender representation in the music video (MV) “Oshibe to Moshibe” by JKT48, one of Indonesia’s most prominent idol groups. Employing a framing analysis approach in conjunction with Standpoint Theory and Muted Group Theory, this study highlights how women’s experiences and expressions are shaped and constrained by an idol industry that remains dominated by a male perspective. The findings indicate that although the MV presents a female-centered narrative with non-heteronormative sexual themes, its representation remains framed by masculine industry standards, resulting in women’s voices being rendered muted and incomplete. The controversies surrounding the MV reveal the challenges involved in negotiating the boundaries of gender expression within Indonesian popular culture, while simultaneously provoking broader discussions on gender fluidity and audience perception.Furthermore, the choreography and bodily gestures are c haracterized by softness and restraint, yet are imbued with strong emotional significance. The female body is represented as the primary medium for articulating inner conflict, while gender relations are naturalized through biological metaphors that position desire as something inherent and inevitable. This study also finds that visual framing and lyrical narratives tend to reproduce traditional gender constructions, in which women are positioned as bearing the moral burden within romantic relationships. Thus, the music video and its lyrics not only reflect emotional experiences but also contribute to the maintenance of dominant gender discourses, particularly those originating from the Japanese idol industry and reproduced within the Indonesian music industry.Keywords: Gender Representation, Idol Industry, JKT48, Music video, Male gaze, Standpoint Theory, Muted Group Theory, Gender Fluidity, Indonesian Pop Culture.